Linear elastic waves - Harris, John G. (Cambridge texts in applied mathematics., 2001)
"Wave propagation and scattering are among the most fundamental processes that we use to comprehend the world around us. Whereas these processes are often very complex, one way to begin to understand them is to study wave propagation in the linear approximation. This is a book describing such propagation using, as a context, the equations of elasticity. Two unifying themes are used. The first is that an understanding of plane wave interactions is fundamental to understanding more complex wave interactions. The second is that waves are best understood in an asymptotic approximation where they are free of the complications of their excitation and are governed primarily by their propagation environments.